Penerapan Uji Proporsionalitas Dalam Kasus Pembubaran Partai Politik: Sebuah Perbandingan - -, Bisariyadi (Jurnal Hukum & Pembangunan, 2018)
The Indonesian Constitutional Court has no jurisprudence related to the application of proportionality test. In comparative law perspective, proportionality test is referred to as "the ultimate rule of law”. This study aims to provide a consideration to the possibility of applying proportionality test when the Constitutional Court needs to deals with the issue of political parties dissolution. In countries that have examined cases of political parties dissolution, the proportionality test is a method of legal reasoning to reach the decision. This studyis conducted by comparing verdicts from national and regional courts, which have dealt with the dissolution of political parties and applying proportionality test.